The Influence of Wages, Human Development Index, And Gross Regional Domestic Product on Poverty in Provinces in Indonesia - Pratama, Andika; Ratih, Arivina (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The main goal of this study is to ascertain how poverty is affected in 16 Indonesian provinces by which is the Human Development Index, gross regional product, and minimum salaries in each province. Multiple linear regression analysis is the method utilized for analysis. The Fixed Effect Model is the estimate technique used for panel regression models. The analysis’s findings demonstrate that the provincial minimum wage has no discernible impact on poverty, indicating that raising the minimum wage does not always translate into more prosperity or a decline in poverty. In the meantime, poverty is negatively impacted by both the Human Development Index and the Gross Regional Domestic Product, which means that poverty is significantly negatively impacted by both the HDI and GRDP.